3-cyclohexyloxy-2-hydroxypropyl acrylate-styrene copolymers: Synthesis, characterization, and reactivity ratios - Coskun, M; Erten, H; Ozdemir, E; Ahmedov, MA (Marcel Dekker Inc, 1997)
Copolymers of 3-cyclohexyloxy-2-hydroxypropyl acrylate (HHPA) with styrene were prepared by free-radical-initiated solution polymerization in 1,4-dioxane. H-1 and C-13 nuclear magnetic resonance techniques were used in the polymer characterization. Glass transition temperatures as a function of HHPA in copolymer changed from 76 to 17 degrees C. The copolymer compositions were determined by elemental analysis and H-1-NMR spectra. Reactivity ratios were calculated as r(HHPA) = 0.37 +/- 0.34 and r(styrene) = 1.10 +/- 0.47 from the Kelen-Tudos equation, and r(HHPA) = 0.31 +/- 0.08 and r(styrene) = 0.95 +/- 0.37 from the Fineman-Ross equation.